A adoção de práticas cooperativas pela Advocacia Pública: fundamentos e pressupostos - Castelo Branco, Janaina Soares Noleto (2018)
The purpose of this thesis is to analyze the causes of the State being the largest judicial litigant in the country, as well as the foundations and assumptions for the adoption of cooperative practices tending to overcome this framework by the Public Attornment. The obstacles to the search for consensuality are investigated from an institutional analysis of Public Attornment. The procedural prerogatives of Public Attornment and of the State are critically examined in order to ascertain whether and to what extent they may be considered legitimate in a context of State cooperation. The new cooperative practices recently introduced in the national legal universe, as well as the peculiarities that these institutes assume when used by public entities and its organs, are presented. According to this research, the main causes for being the State the largest repeat player of the Brazilian justice system are: extensive role of constitutional attributions, judicial activism and cooperation assent. The following grounds for the adoption of cooperative practices are concluded: public interest and principles of administrative morality, administrative good faith and trust protection. It is found that several prerogatives are necessary so that the Public Attornment can consolidate itself as an internal control organ extra-power and exercise with greater autonomy its mister, which is a presupposition for the adoption of cooperative practices. It is found that the most controversial prerogatives of Public Attonrment and of public entities are legitimate only if necessary to the achievement of public interest because of peculiarities of State activity. It is analyzed the behavior expected of the Public Administration in the chambers of prevention and administrative resolution of disputes. It is concluded that it is possible to celebrate conventions regarding several prerogatives, as well as the binding nature of the Public Administration to the mandatory judicial precedents, not being denied, however, a strategic action to reverse them prior to surrender. Papers and works related to the subject were investigated, as well as legislation, jurisprudence – especially of higher courts – and statistical data collected by the National Council of Justice. The collected material was submitted to a critical-constructive analysis, in order to confront contradictory arguments to present viable proposals to solve the presented problem.